FAKTOR â FAKTOR YANG MEMPENGARUHI PERFORMANCE OF ACCOUNTING INFORMATION SYSTEMS - Samrotun, Yuli Chomasatu (PARADIGMA, 2014)
Target in this research is to know the wearer involvement in system development accounting information, training or education of wearer and management support culminate to have an effect on by parsial to performance of information system accountancy and To know the wearer involvement in system development accounting information, training or education of wearer and management support culminate to have an effect on by simultan to performance of information system accountancy. Sampel used in this research responder using information system accountancy at dealer Honda, Yamaha, Suzuki and Kawasaki amounting to 60 responder part of administration. Pursuant to result of hypothesis 1 proved result test known that the variable of wearer involvement have the influence by parsial and signifikan to performance information system accountancy., variable program the training and education have the influence by parsial and signifikan to performance information system accountancy, and variable of support manejemn culminate the top have the influence by parsial and signifikan to performance information system accountancy. While to result of hypothesis 2 proved that variable of wearer involvement in system development accounting information, training or education of wearer and management support culminate to have an effect on by simultan to performance information system accountancy. While this research own the limitation that is limited to accurate variable that is only wearer involvement, training and education and support manejemen culminate in influencing performance information system accountancy, research area that is regional karesidenan Surakarta.Â Keyword :Â Â Â Â Wearer Involvement, Training Or Wearer Education, Management Support Culminate and Performance of Information System Accountancy.